Youtube Influencer on use Itention with Brand Love Using Word of Mouth - Ahmad Husein; Kukuh Ardian Huda; Husna Leila Yusran (Cakrawala Repositori IMWI, 2023)
Youtube is still the top streaming platform in Indonesia in particular, which is accompanied by the rapid growth of creative workers who are engaged in content creation in the last few years. The presence of celebrity YouTubers is one of the most effective marketing strategies to market various brands to increase interest in using products. YouTube is a relevant channel for advertising and promoting a brand. Hence, the company should bear in mind the fact that the YouTuber appointed to represent its image must be connected to the feelings and interests of their followers as well as those of the brands to be publicised. The present study reveals that the follower’s engagement with YouTubers presents itself within cognitive, affective and behavioural aspects, it rises from the involvement the followers have with theirfavourite YouTuber, impacts the brand love, word of mouth and intention of use of a brand he/she indicates or uses. Planned behavioral theories track attitudes, subjective norms, and perceived behavioral control, based on the underlying foundations of behavioral beliefs. These intentions, combined with perceived behavioral control, can account for a significant proportion of behavioral changes, using planned behavior theory, the problem is solved. This study aims to examine the role of the variable brand love and word-of-mouth as a mediation for use intention through Youtube Influencers.